Analisis Efektivitas Dan Efisiensi Realisasi Anggaran Pendapatan Dan Belanja Daerah Pada Dinas Koperasi Dan UKM Provinsi Jawa Timur - Rajendra Ghazian Zhafiri; Sri Trisnaningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to analyze and find out the level of effectiveness and efficiency in the realization of the regional income and expenditure budget at the Office of Cooperatives and UKM of East Java Province for the 2019 – 2021 fiscal year. This research uses a descriptive research method with a quantitative approach. The type of data in this study is secondary data in the form of a report on the realization of the regional income and expenditure budget. Data collection techniques in this study used the documentation method. This study obtained the results that the effectiveness of the realization of the regional original revenue budget at the Office of Cooperatives and UKM of East Java Province in 2019 and 2020 has very effective criteria and 2021 has criteria that are quite effective. Meanwhile, the level of efficiency in the realization of the 2019-2021 regional budget is less efficient. Keywords: Effectiveness, Efficiency, Budget, APBD